GMAT GRE 1st Grade 2nd Grade 3rd Grade 4th Grade 5th Grade 6th Grade 7th grade math 8th grade math 9th grade math 10th grade math 11th grade math 12th grade math Precalculus Worksheets Chapter wise Test MCQ's Math Dictionary Graph Dictionary Multiplicative tables Math Teasers NTSE Chinese Numbers CBSE Sample Papers 
Common and Natural LogarithmCommon and natural logarithm have base 10 and base 'e' respectively.There are two bases in logarithm. One base is 10 and other base 'e'. The logarithm with base 'e' is called natural logarithm. The value of e ≈ 2.71828183. The logarithm with base 10 is called common logarithm. Common logarithm : In this logarithm the base is 10. 1) log 10 ^{n} = n 2) log 10 ^{2} = 2 3) log 10 ^{3} = 3 4) log 10 ^{4} = 4 5) log 1000 =log 10 ^{3} = 3 6) log 1 = log 10 ^{0 } = 0 7) log 0.1 = log 10 ^{1 } = 1 Natural Logarithm : It is a logarithm with base 'e'. It is denoted by ln (x) . If e ^{y} = x By definition of natural logarithm, here the base is 'e', So log _{e} = y OR ln (x) = y Rules and properties of common and natural logarithm are same .Product Rule (1st rule) : ln(mn) = ln (m) + ln(n)Proof : Suppose ln(m) = x and ln(n) = y e ^{x} = m and e ^{y} = n ∴ mn = e ^{x} . e ^{y} mn = e ^{x + y} By definition of natural logarithm ln(mn) = x + y ln(mn) = ln(m) + ln(n) Example : Find : ln(7) + log 3 Solution : Consider ln 7 + ln 3 ln (7 x 3 ) > By 1st rule = ln 21 ∴ ln(21) = ln 7 + ln 3 Quotient rule (2nd rule): ln(m/n) = ln (m)  ln(n) Proof : Suppose ln(m) = x and ln(n)= y e ^{x} = m and e ^{y} = n ∴ m/n = e ^{x} / e ^{y} m/n = e ^{x  y} By definition of natural logarithm ln(m/n) = x  y ln(m/n) = ln(m) ln(n) Example : Find ln (8)  ln(2) Solution : Consider ln 8  ln 2 ln 8  ln 2 = ln(8/2) > By 2nd rule of natural logarithms = ln (4) ln (8)  ln(2) = ln (4) Power rule(3rd rule): ln(m)^{n} = n ln(m) Proof : Suppose ln(m) = x e ^{x} = m (e ^{x} ) ^{n} = (m) ^{n} ( taking nth power on both sides) By definition of natural logarithm ln(m) ^{n} = n. x ln (m) ^{n} = n . ln m Example : Find ln (8) ^{2} Solution : ln (8) ^{2} = ln (2 ^{3} ) ^{2} = ln (2 ^{6} ) = 6. ln 2 (by 3rd rule ) 4th rule : ln (1)= 0 5th rule : ln (x) is undefined when x≤ 0 so ln(0) is undefined. From common and natural logarithm to Home page
More To Explore
